(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article conducts a comparative analysis of the creedal positions advanced by contemporary pseudo-Salafi movements and their ideological affinity with the historical mushabbiha and mujassima sects of Islamic intellectual history. Despite pseudo-Salafis’ self-presentation as defenders of pure creed, the article demonstrates that their doctrinal roots lead back to the deviant sects of earlier Islamic history. Five principal areas of ideological convergence are identified: the literal interpretation of mutashabih Qurʼanic expressions; the attribution of direction and locality to Allah; the attribution of movement and change to Allah; the rejection of taʼwil combined with false attribution to the pious ancestors; and the use of takfir ideology. The article further identifies the Karramiya sect of Muhammad ibn Karram al-Sijistani (d. 255/868) as the historical movement most closely aligned with contemporary pseudo-Salafism. The study concludes that pseudo-Salafism represents not a continuation of the methodology of the genuine pious ancestors but a modern revival of the doctrinal positions of the historically deviant mushabbiha, mujassima, and Karramiya movements, and that the critiques formulated by Imam al-Maturidi and Imam Abu al-Muʿin al-Nasafi remain directly applicable to their contemporary positions.